Analisis Kesalahan Fonologi Dalam Pengucapan Huruf Hijaiah Pada Penderita Gangguan Pendengaran Sensorineural - Aqmarina Allail, Cindy; Maulani , Hikmah; Syihabuddin , Syihabuddin (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The aim of this research is to determine the characteristics of the pronunciation of makhorijul letters for people with sensorineural hearing loss or SNHL.Â  A person with SNHL has hearing problems and this affects their phonological speech. This research is a qualitative descriptive study with the data source being an adult man with the initials NH who is 30 years old. The data collection technique used is the listening and speaking technique. Data were analyzed using the Miles and Huberman model, namely data reduction, data presentation, and conclusion verification. The results of this study show that people with sensorineural hearing loss experience many errors in pronunciation of hijaiah letters, especially in makhroj al-lisan for letters of the same nature. These errors are based on the makhorijul letters which are divided into al-jauf (mouth cavity), al-halaq (throat), al-lisan (tongue), ash-syafatain (two lips), and al-khaisyum (bridge of the nose). In Arabic vocabulary phonemes, 3 phonological errors were found, namely addition, subtraction and replacement of phonemes. Sensorineural hearing loss in this study was caused by frequent blows to the head and taking certain medications, resulting in sound waves that were captured not being heard perfectly and experiencing errors in the phonological aspect. Â